SARS Covid-19- Call of Threat: Attributes and Current Approach - Anima Mathur; Deepti Sadana; Gauhar Azad (International Journal of Pharma and Bio Sciences, 2021)
COVID -19 disease (Coronavirus) is a contemporary strain of coronavirus species which has initially appeared in Wuhan city, China. Over the few months it has spread to various regions of the world. It is observed that COVID-19 is able to get transmitted from human to human contact, by means of droplets sustained in the air as aerosols, fomites etc. WHO (World Health Organization) has declared the current outbreak to be a public health emergency globally. As the disease is life threatening, there is a crucial need for effective drugs. Optimistic nurture remains the backbone of the therapy. Despite the COVID-19 patients having benign or mild courses, up to 5% –10% can have serious; probably life alarming courses, there is a crucial need for effective drugs. There have been several clinical trials persisting, various immune regulating and antiviral agents for assessments of COVID-19 in those investigations and some of them would be reported in later couple of days. Although the critical need to find an efficient antiviral medication for COVID-19 through randomized controlled investigation, certain agents are being utilized all over the world, established on either envisioned evidence, in vitro or experimental studies. Presently, the research investigation on SARS COVID-2 is in the initial stages. Based on ongoing published information, this review article consistently summarizes the pathological analysis, clinical symptoms, prevention and treatment of COVID-19. Generally, maximum used therapeutic agents in India and all over the world includes hydroxychloroquine, chloroquine, remdesivir, favipiravir, lopinavir and Nitazoxanide. This review reports about Ivermectin to have an activity against SARS-COVID-19 in vitro, which is permitted for some other treatments of human diseases. It is assumed that this review will encourage the nation to recognize and handle COVID-19 and contribute for prospective studies.